Monitoramento acústico passivo através de matriz de arrasto: detecção, localização, perfil de mergulho e estimativa da densidade de baleias cachalote (Physeter macrocephalus) na plataforma continental externa e talude sul brasileiro - Castro, Franciele Rezende de (Universidade Federal de Juiz de Fora (UFJF), 2018)
In face of new potential threats from anthropogenic activities introduced in all oceans worldwide, the monitoring of marine fauna species, such sperm whales, is imminent. This species typically spends 70 to 75% of its time in foraging dives, becoming difficulty to observed. However, while diving individuals produce foraging vocalizations, which make them amenable to acoustic monitoring. In recent years, Passive Acoustic Monitoring (PAM) have been increasingly applied. Results from the first sperm whale PAM effort carried out in the southern Brazilian outer continental shelf and slope are presented here. Three ship-based surveys were conducted using a 3-element towed array. Sperm whale click trains were detected and located using PAMGuard. This species acoustic encounters occurrence and distribution in relation to stationary and anthropogenic features were spatially assessed, and its abundance estimated through Conventional Distance sampling (CDS) analysis. Moreover, data from five Time-Depth Recorders (TDR’s) attached in sperm whales off Brazil were used to assess this species dive profile and five Digital Tags (Dtags) placed in individuals around Azores were used to directly estimate the percentage of time individuals were acoustically available. The joint assessment of both tag types allowed to estimate the detection probability at zero horizontal distance g(0). From 21 acoustic encounters recorded, 57% were beyond the 1000 meters (m) isobath, with 85.71% (n = 18) occurring between the slope limits of the 200 m and 2000 m isobaths. Seven recordings (33.33%) occurred in oil and gas blocks. In contrast, all acoustic encounters were recorded in Priority Areas for Conservation (PACs). The best-fitted generalized linear model (GLM) indicated depth as the only covariate with a significantly positive relationship to sperm whale acoustic encounters distribution. A total of 139 complete dives were used to assess this species dive profile. V-shaped shallow dives (40.29%) were the most frequent dive type, followed by ...